(untitled) (The Journal of Geography Education in Africa, 2022)
This study aimed to interrogate the place of TikTok, memes, and YouTube in the geography classroom. The literature reviewed constructed today’s learner as one born within a digital age. This qualitative study was guided by the theory of multimedia learning and the continuum of meaning. The study fell under the interpretivist paradigm. Data was generated using artefact-based interviews. The study established that YouTube, TikTok, and memes enhance geography teaching in the 21st-century classroom. It was also noted that YouTube, memes, and TikTok appeal to multiple senses and promote effective learning. The study also identified benefits and pitfalls in integrating TikTok, memes, and YouTube in teaching geography. Drawing from the findings, this paper recommends that learners’ prior knowledge inform ICT integration in the geography classroom of the tools used to teach.